Integrated bioconversion of pulp and paper primary sludge to second generation bioethanol using Saccharomyces cerevisiae ATCC 26602 - Mendes, Catia V. T. (2016)
Primary sludge, from different pulp and paper mills, was used as feedstock in simultaneous saccharification and fermentation (SSF) processes to produce ethanol. SSF was carried out with Saccharomyces cerevisiae ATCC 26602 yeast and NS 22192 enzymatic extract using 150 g L-1 of carbohydrates (CH) from primary sludge. The effect of sterilization, reduction of enzyme dosage and fed-batch vs. batch conditions were studied. The removal of sterilization can be considered since no contamination or atypical by-products were observed, although SSF efficiency slightly decreased. The reduction of the enzyme dosage from 35 to 15 FPU g(CH)(-1) was successful. Despite of initial mixing difficulties, batch SSF enabled higher ethanol concentration (41.7 g L-1), conversion yield (48.9%) and productivity (0.78 g L-1 h(-1)), compared to the fed-batch process at the same conditions of low enzyme dosage of 5 FPU g(CH)(-1) and high solids content of 21.7%, rarely found in literature. Published by Elsevier Ltd.